Morphologies, Mechanical Properties and Thermal Stability of Poly(lactic acid)/Waste Rubber Powder Blends - Yang, Jinian; Ding, Guoxin; Wang, Zhoufeng; Wang, Chuang (Asian Journal of Chemistry, 2014)
Poly(lactic acid) (PLA) blends containing varied mass fraction of waste rubber powder (WRP) were fabricated by melt compounding. Moreover, the morphologies, mechanical properties and thermal stability of the samples were investigated systematically. SEM observation shows that the well bonded interfacial structures between PLA and WRP particles are observed with the aid of silane coupling agent. Mechanical tests point out that the WRP could increase the impact toughness with the content up to 15 %. However, only a slight improvement in tensile strength when WRP content reaches 10 % and the elastic modulus is decreased continuously with the rise of WRP. Thermogravimetric analysis shows the thermal decomposition temperatures of blends are declined gradually with WRP loading.